Mulching tree leaves improve the growth, yield, and yield components of hybrid maize (Research in Agriculture Livestock and Fisheries, 2024)
The experiment was carried out at the Agroforestry Farm, Department of Agroforestry, Bangladesh Agricultural University, Mymensingh from November 2019 to March 2020 to assess the impact of tree leaf mulching on the growth, yield attributes, and yield of maize. The study used a Randomized Complete Block Design with three replications and six treatments. These treatments were: T0=Control (no mulch), T1=Akashmoni (Acacia auriculiformis) tree leaf mulch, T2=Segun (Tectona grandis) tree leaf mulch, T3=Kalo koroi (Albizia lebbeck) tree leaf mulch, T4=Jhau (Casuarina equisetifolia) tree leaf mulch, and T5=Jackfruit (Artocarpus heterophyllus) tree leaf mulch. The results showed that the Kalo koroi tree leaf mulch (T3) led to the highest values for various parameters such as plant height, number of effective tillers per plant, number of leaves per plant, leaf length, leaf diameter, number of cobs per plant, length, and diameter of cob, the weight of single cob, number of grains per cob, grain weight per cob, 100-grain weight, and grain yield of maize (221.18 cm, 0.93, 17.29, 79.26 cm, 7.30 cm, 4.18, 1.70, 21.11 cm, 6.08 cm, 212.12 g, 453.85 g, 138.91 g, 30.60 g, and 11.81 t/ha). Conversely, the lowest values were obtained in the control (T0) (no mulch), followed by T2 and T1 treatments (209.39 cm, 0.37, 12.5, 72.48 cm, 4.62 cm, 1.50, 15.03 cm, 4.44 cm, 202.19 g, 421.56 g, 111.55 g, 26.46 g, and 8.35 t/ha). Among the various tree leaf mulch treatments, it was found that the Kalo koroi tree leaf mulch performed better for vegetative growth, yield, and yield-contributing attributes in maize compared to the no mulch treatment. Therefore, it was suggested that tree leaf mulches could be a potential alternative to traditional mulches in maize cultivation.Res. Agric. Livest. Fish. Vol. 11, No. 2, August 2024: 205-214